2022
DOI: 10.1227/ons.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Dura Management Strategies in the Surgical Treatment of Adult Chiari Type I Malformation: A Retrospective, Multicenter, Population-Based Parallel Cohort Case Series

Abstract: BACKGROUND:Symptomatic Chiari I malformation is treated with suboccipital decompression and C1 laminectomy. However, whether the dura should be opened (durotomy) or enlarged with a graft (duraplasty) remains unclear.OBJECTIVE:To compare outcomes in adult Chiari I malformation patients treated with duraplasty, durotomy, or without dural opening (“mini-decompression”).METHODS:A retrospective, multicenter, population-based cohort study was performed of all adult patients surgically treated for a Chiari I malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Importantly, the advantage of durotomy lies in re-establishing the normal CSF circulation by providing a wide exposure to allow for microlysis of adhesions that can tether the tonsils, brainstem, spinal cord, and posterior inferior cerebellar artery, along with tonsillar reduction when needed. 3 In the current study, 1 both duraplasty and durotomy alone were accompanied by a sharp arachnoid membrane dissection.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Importantly, the advantage of durotomy lies in re-establishing the normal CSF circulation by providing a wide exposure to allow for microlysis of adhesions that can tether the tonsils, brainstem, spinal cord, and posterior inferior cerebellar artery, along with tonsillar reduction when needed. 3 In the current study, 1 both duraplasty and durotomy alone were accompanied by a sharp arachnoid membrane dissection.…”
mentioning
confidence: 76%
“…T he authors should be commended for presenting a unique, retrospective, population-based cohort study of patients treated surgically for Chiari type I malformation at 3 neurosurgical centers in Sweden. 1 Of 318 adult patients enrolled, 166 (52%) treated with posterior fossa decompression (PFD) and duraplasty were compared with 118 (37%) treated with PFD and durotomy alone, with only 34 (11%) undergoing PFD alone, without durotomy. PFD bone-only patients were excluded due to their low sample size.…”
mentioning
confidence: 99%
“…[ 4 , 5 ] The goals of surgery are to relieve pressure on the relevant hindbrain structures and to restore the normal cerebrospinal fluid (CSF) flow across the craniovertebral junction, which is most commonly done by decompression of the posterior fossa and foramen magnum. [ 5 6 7 ] Reasons for CM reoperation include persisting neurological symptoms, inadequate initial decompression, faulty stent placements, and development of postoperative complications. [ 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…a Kristiansson et al[35] reported the use of sutured biological patch with addition of an overlayed synthetic patch; b Bowers et al[25] reported 128 procedures on 119 patients.…”
mentioning
confidence: 99%